Pembagian Hak Atas Tanah Waris dalam Hukum Adat Bali - I Putu Angga Aptina; Anak Agung Istri Agung; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
The issue of inheritance disputes among the village community is very frequent. For this reason, written and unwritten laws are needed for the implementation of a fair distribution of inheritance for each people. The research method used is the Empirical research method, the approach is to see the law in a real sense or it can be said to see researching how the law works in society. The results showed that as a manifestation of mutual respect and an attitude of living in harmony, always strived for dispute resolution through family deliberations. Peaceful settlement is prioritized to maintain balance in social life. Peaceful resolution is also intended to eliminate feelings of resentment resulting from disputes that arise. Peaceful settlement in life in the village is seen as necessary and a necessity to maintain harmony in dispute resolution. It is hoped that the problem can be resolved amicably in a friendly manner.